The Effect of Phase Change Material on Recovery of Neuromuscular Function Following Competitive Soccer Match-Play - Brownstein, Callum G.; Ansdell, Paul; Škarabot, Jakob; McHugh, Malachy P.; Howatson, Glyn; Goodall, Stuart; Thomas, Kevin (Frontiers in Physiology, 2019)
Aim: Cryotherapy is commonly implemented following soccer match-play in an attempt to accelerate the natural time-course of recovery, but the effect of this intervention on neuromuscular function is unknown. The aim of the present study was to examine the effect of donning lower-body garments fitted with cooled phase change material (PCM) on recovery of neuromuscular function following competitive soccer match-play. Methods: Using a randomized, crossover design, 11 male semi-professional soccer players wore PCM cooled to 15°C (PCMcold) or left at ambient temperature (PCMamb; sham control) for 3 h following soccer match-play. Pre-, and 24, 48, and 72 h post-match, participants completed a battery of neuromuscular, physical, and perceptual tests. Maximal voluntary contraction force (MVC) and twitch responses to electrical (femoral nerve) and magnetic (motor cortex) stimulation (TMS) during isometric knee-extension and at rest were measured to assess central nervous system (CNS) (voluntary activation, VA) and muscle contractile (quadriceps potentiated twitch force, Qtw,pot) function. Fatigue and perceptions of muscle soreness were assessed via visual analog scales, and physical function was assessed through measures of jump [countermovement jump (CMJ) height and reactive strength index (RSI)] performance. A belief questionnaire was completed pre- and post-intervention to determine the perceived effectiveness of each garment. Results: Competitive soccer match-play elicited persistent decrements in MVC, VA measured with femoral nerve stimulation, Qtw,pot, as well as reactive strength, fatigue and muscle soreness (P < 0.05). Both MVC and VA were higher at 48 h post-match after wearing PCMcold compared with PCMamb (P < 0.05). However, there was no effect of PCM on the magnitude or time-course of recovery for any other neuromuscular, physical function, or perceptual indices studied (P > 0.05). The belief questionnaire revealed that players perceived that both PCMcold and PCMamb were moderately effective in improving recovery, with no difference between the two interventions (P = 0.56). Conclusion: Although wearing cooled PCM garments improved MVC and VA 48 h following match-play, the lack of effect on measures of physical function or perceptual responses to match-play suggest that PCM offers a limited benefit to the recovery process. The lack of effect could have been due to the relatively small magnitude of change in most of the outcome measures studied.